De R.K. hbs voor Meisjes te Amsterdam: Katholieke emancipatie in het interbellum - Streefland, Aad (Studium, 2018)
The first Roman Catholic HBS for girls in the Netherlands was founded in 1914 by the Sisters Franciscans of Heythuysen, at the request of the Catholic elite of Amsterdam. The school grew so fast that already in 1925 a new building on the Reynier Vinkeleskade was opened.  The character of the HBS made the school not only a breeding ground for Catholic women’s emancipation, but also a place where girls could study the medical and the exact sciences. Some of them became the first female doctors and laboratory workers in Amsterdam. Initially, the school had an elitist character, but from the moment the school became a ‘lyceum’ in 1926, students from other layers of the (Catholic) population started to come to the school. With the opening of an MMS-department in 1952 the school got a new name: Fons Vitae Lyceum. It still exists under that name.